1998
DOI: 10.1063/1.121241
|View full text |Cite
|
Sign up to set email alerts
|

Observation and creation of current leakage sites in ultrathin silicon dioxide films using scanning tunneling microscopy

Abstract: We used scanning tunneling microscopy (STM) to investigate the local leakage current through ultrathin silicon dioxide (SiO2) films grown on Si substrates. Individual leakage sites, which were created by hot-electron injection from the STM tip under a high sample bias of +10 V, were identified from the local change in surface conductivity due to defect creation in the oxide films. When we reversed the stressing polarity (using a negative sample bias) no leakage sites were created in the oxide film.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 14 publications
1
48
0
1
Order By: Relevance
“…Our experiments show a nonlinear ͑nonmetallic͒ conductance at the leakage site, similar to observations by Watanaba et al on silicon oxide films. 7 However, in our case a reversible behavior of the switching was observed, which may be considered as a precursor of the soft breakdown. Additionally, we like to add that the dimension of the leakage sites (ϳ2 nm) is in excellent agreement with predictions by Oepts et al, 16 who estimated a diameter of a few nanometers from macroscopic breakdown experiments.…”
Section: Stm-induced Reversible Switching Of Local Conductivity In Thmentioning
confidence: 95%
See 1 more Smart Citation
“…Our experiments show a nonlinear ͑nonmetallic͒ conductance at the leakage site, similar to observations by Watanaba et al on silicon oxide films. 7 However, in our case a reversible behavior of the switching was observed, which may be considered as a precursor of the soft breakdown. Additionally, we like to add that the dimension of the leakage sites (ϳ2 nm) is in excellent agreement with predictions by Oepts et al, 16 who estimated a diameter of a few nanometers from macroscopic breakdown experiments.…”
Section: Stm-induced Reversible Switching Of Local Conductivity In Thmentioning
confidence: 95%
“…4 More interestingly, it was found that applying a positive sample bias ͑electrons from tip to sample͒ of several volts leads to the irreversible formation of spots with an enhanced local conductivity. 7 In the more severe cases, large regions with a diameter of tens of nanometers and linear ͑metallic͒ current-voltage (I-V) characteristics were created. 4 In some of the studies smaller, though irreversible, leakage sites were induced that displayed nonmetallic transport properties.…”
Section: Stm-induced Reversible Switching Of Local Conductivity In Thmentioning
confidence: 99%
“…The bond energy of Si-O in SiO 2 is 6.5 eV; therefore, the current injection from the STM-tip can cut the Si-O bond. However, the STM could not decompose the thermally oxidized surface [20]. The difference should be caused by the difference of defect density.…”
Section: Resultsmentioning
confidence: 99%
“…The SiO 2 decomposition by the e-beam is believed to follow the reaction 2SiO 2 → O 2 ↑ +2SiO ↑ [15] and does not consume bulk Si atoms to reduce SiO 2 . Furthermore, the extreme condition of STM observation (bias voltage V s = +10 V, tunnel current I t = 6 nA) created a leakage site of current on the thermal oxide layer [20]. For this phenomenon to occur, it is believed that the injection of electrons into a defect, which acts as an electron trap site, is essential [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation